Improving Soil Quality and Crop Yields Using Enhancing Sustainable Rice Straw Management Through Microbial Enzyme Treatments - Van-Phuc Dinh; Hoai-A; Thanh Tran; Bich-Ngoc Duong; Ngoc-Ma; Hoai-Lua; Tuan-Kiet Tran; Van-Hieu Huynh; Thi-; Thanh Q Nguyen (SAGE Publishing, 2024)
This study develops a model to raise public awareness about the consequences of burning rice straw after harvest, including environmental pollution, soil degradation, and increased CO 2 emissions that contribute to the greenhouse effect. The distinctive feature of the research is the introduction of a post-harvest rice straw treatment process using microbial products capable of secreting cellulase enzymes, which can break down the cellulose in the straw. This process shortens the decomposition time and produces natural organic fertilizer, thus reducing cultivation costs by 60% and increasing crop yields by 20%. The experimental model was carried out in Cam My district, Dong Nai province, Vietnam, including 4 models: no microbial products; using Bio Decomposer; using NTT-01; and using NTT-02. Each experimental field had an area of 650 m². The results showed a significant reduction in straw decomposition time after 14 days of use of the products, with a decomposition rate of up to 80%, nearly twice as fast as without the products. This helps save time, produce natural organic fertilizers, reduce care costs, and increase rice yields, resulting in more income for local residents. These findings demonstrate the effectiveness of microbial treatments in sustainable agriculture and their potential for a broader application in the management of agricultural waste.